Molecular Tumor Board - Lamichhane, Nirmal (Nepalese Journal of Cancer, 2021)
A tumor board is a meeting made up of specialized doctors and other health care providers who regularly gather to discuss cancer cases that are unusual and/or challenging. The goal is to decide on the best possible treatment plan for a patient as a group. This has become a very systematic method in cancer care and is useful in picking up all the available information about the patients, inputs of all concerned doctors and other health care personnels. Molecular Tumour boards are where the molecular informaion about the patients are discussed.